Buccal Pedicle Flap Technique Combined With Porcine Collagen Matrix for Volumetric Augmentation of Peri‐Implant Mucosa. Issue 1 (5th November 2020) - Tabanella, Giorgio
Abstract : Introduction: A special interest has been raised regarding the role of the peri‐implant mucosa as a critical factor for long‐term maintenance of the artificial fixtures as well as the final esthetic outcome that may significantly affect patient satisfaction. It is then imperative to develop minimally invasive and easy‐to‐apply plastic surgical methods to increase the volume of the peri‐implant mucosa. Case Presentation: The limited scientific evidence regarding possible techniques to treat esthetic soft tissue defects around endosseous implants is encouraging a preventive soft tissue augmentation of mucosa deficiencies and thin phenotypes. Several techniques have been proposed to augment the volume of the mucosa to achieve the so‐called pink esthetics. Among these the buccal pedicle flap seems to be less invasive in terms of morbidity since it does not necessitate any soft tissue harvesting. Its low morbidity allows it to treat patients without the need of postoperative medications since it reduces pain, the risk of infections, alteration of the sensitivity of the donor site and significantly reduces the period of healing which is generally longer when associated with connective tissue grafts. A modified surgical approach is based on the combination of the buccal pedicle flap with a stable collagen matrix to boost a biomimetic peri‐implant mucosa and generate a convex pink interface with the final restoration. Conclusion: The proposed modified buccal pedicle flap seems to be promising in terms of decreased morbidity and maintenance of the blood supply, and conducive to an increased patient acceptance rate.